MEMPERKAYA BETA KAROTEN, ZAT BESI PADA MIE KERING DENGAN BAYAM RAJA DAN KARAKTERISTIK FISIKNYA - Endang Bekti K; Dewi Larasati (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2005)
Amaranthus hybriduspaniculatus L (bayam raja) flour seems have a potential effect for β caroten and iron fortification on dried noodle. Because, β caroten and iron content on bayam raj a flour is about 36294, 7 µgl I 00 g and 28,5 ppm respectively. The dried noodle made from bayam raja there flour substitution is inrich with Bcaroten and iron. The increase, of flour substitution flour on the noodle, β caroten and iron inrichment. There is also existence of high protein and fiber. How ever the excessive use of substitution will decrease the dried noodle tensil strength. Substitution recomemended for inrich the dried noodle with bayam raja flour β caroten and iron, optimal used for substitution flour around 2-4 %.